2014
DOI: 10.1242/jcs.149369
|View full text |Cite
|
Sign up to set email alerts
|

Dendrite architecture organized by transcriptional control of the F-actin nucleator Spire

Abstract: The architectures of dendritic trees are crucial for the wiring and function of neuronal circuits because they determine coverage of receptive territories, as well as the nature and strength of sensory or synaptic inputs. Here, we describe a cell-intrinsic pathway sculpting dendritic arborization (da) neurons in Drosophila that requires Longitudinals Lacking (Lola), a BTB/POZ transcription factor, and its control of the F-actin cytoskeleton through Spire (Spir), an actin nucleation protein. Loss of Lola from d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…First, terminal branch distribution along the proximal-distal axis depends on microtubule-based processes; perturbing microtubule-based transport leads to a distal-proximal shift in the distribution of terminal dendrites in C4da arbors (Satoh et al, 2008;Zheng et al, 2008). Interestingly, modulating the activity of the F-actin nucleator Spire also affects terminal dendrite positioning along the proximal-distal axis (Ferreira et al, 2014), suggesting that multiple pathways contribute to the fidelity of branch placement. Second, terminal dendrites rely on dedicated programs that may act locally to regulate terminal dendrite patterning.…”
Section: Discussionmentioning
confidence: 99%
“…First, terminal branch distribution along the proximal-distal axis depends on microtubule-based processes; perturbing microtubule-based transport leads to a distal-proximal shift in the distribution of terminal dendrites in C4da arbors (Satoh et al, 2008;Zheng et al, 2008). Interestingly, modulating the activity of the F-actin nucleator Spire also affects terminal dendrite positioning along the proximal-distal axis (Ferreira et al, 2014), suggesting that multiple pathways contribute to the fidelity of branch placement. Second, terminal dendrites rely on dedicated programs that may act locally to regulate terminal dendrite patterning.…”
Section: Discussionmentioning
confidence: 99%
“…Mutation of lola results in increased spire expression, as well as decreased ISNb motor neuron innervation of ventrolateral musculature, and this phenotype was rescued by heterozygosity for spire (Gates et al, 2011;Madden et al, 1999). It has also been shown that Lola represses expression of spire in dendritic arborization neurons of the PNS, thereby limiting the formation of F-actin branches and controlling branch arrangement in dendritic arbors (Ferreira et al, 2014). The expression of most known Lola isoforms in projection neurons of the developing olfactory system and the requirement for Lola in dendrite and axon targeting in these neurons suggest that Lola is a key transcriptional regulator of the cytoskeleton during nervous system development (Spletter et al, 2007).…”
Section: Lola Serves As a Transcriptional Regulator In Gonad And Nementioning
confidence: 99%
“…One shared upregulated target of Ab and Knot that emerged from this analysis was the BTB/POZ transcription factor Lola, and a subsequent study by van Meyel and colleagues demonstrated that Lola controls dendritic morphogenesis through the actin nucleating protein Spire (Ferreira et al, 2014). Lola is expressed in all classes of da neurons, where it is required for dendritic branching and growth.…”
Section: Transcriptional Regulation Of Morphology In Drosophila Dendrmentioning
confidence: 89%